Adaptive survival mechanisms of Lithops sp. in arid environments: Morphological and water regulation strategies - Sani, Luthfiana Mutiara; Farrennina, Tasya Preira; Yang, Haoling; Putri, Aura Balqis Nicheta; Afidah, Yusfi; Mustafidah, Qori’atul; Mukhamad Su'udi (Teknosains: Media Informasi Sains dan Teknologi, 2025)
Succulents are plants whose body parts are thicker and fleshier as adaptation form to the arid environment in which they grow. Lithops sp. is a succulent plant often found in South Africa and Namibia. This plant belongs to the Aizoaceae family and has a total of 37 species. This study was carried out by collecting reference sources which were then used as a reference for studying Lithops sp. related to morphological structure and adaptation to extreme environment. Lithops sp. shaped like an inverted cone with the part above the ground being the surface of the leaves. This form is an adaptation carried out by Lithops sp. to reduce exposure to sunlight and prevent excess water loss during the transpiration process. Apart from its shape, the epidermis of Lithops sp. also undergoes special differentiation so that it can prevent excess water loss during transpiration. Lithops sp. also undergoes differentiation to form window cells on the surface of its leaves which function to increase the rate of photosynthesis by increasing sunlight radiation entering the photosynthetic tissue.